Bodies in Formation : An Ethnography of Anatomy and Surgery Education - Prentice, Rachel (Book collections on Project MUSE., 2013)
In Bodies in Formation, anthropologist Rachel Prentice enters surgical suites increasingly packed with new medical technologies to explore how surgeons are made in the early twenty-first century.